Evaluation of galectin-3 and peptidyl arginine deiminase-4 levels in saliva for periodontal health, gingivitis and periodontitis - Ali Abdulrazzaq, Yusur; Omran Ali, Alaa ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2025)
Background: Comparing the saliva levels of galectin-3, peptidylarginine deiminase 4 (PAD4) in individuals with periodontitis and gingivitis and with healthy periodontium was the purpose of this clinical research. Methods: This study was an observational case-control study which was conducted at Al- Aamiriya Specialized Dental Center and Department of periodontics, College of Dentistry, University of baghdad from August, 2024 to November, 2024. (84) systemically healthy and non-smoker individuals consisting of periodontitis (group PD/n = 28), gingivitis (group G/n = 28), and periodontally healthy (group H/n = 28) were recruited for this research. Clinical parameters such as probing depth, clinical attachment level, gingival index, plaque index, and bleeding on probing were recorded in periodontal charts. Enzyme-linked immunosorbent assay method was used in evaluating the saliva levels of galectin-3 and PAD4 for study groups. Results: The saliva galectin-3 total amount was highest in group G3 compared with group G1 and group G2 (p<0.05) and in G2 higher than G1.The saliva PAD-4 total amounts were highest in group G3 compared with group G1 and group G2 (p<0.05) and in G2 higher than G1. Conclusions: Galectin-3 and PAD4 may be involved in the periodontal disease pathogenesis considering the elevated levels of these molecules in periodontal disease. These biomarkers may be used in the diagnosis of periodontal diseases.